Experiência e educação escolar em John Dewey (1859 - 1952) - Biasotto, Karine (2016)
In this dissertation we examined the conception of experience and school education in John Dewey (1859-1952). Our objective it was analyze these concepts with finality to understand the relation between the knowledge that comes from practical contemporary experience, linked with the relation in which the individual it is inserted and the knowledge that comes from the historical experience accumulated by the humanity. Considering the proposed, we developed the essay in three chapters. At the first one, we situate the author’s thought in the social context and theoretical of north american society at final decades of XIX century and the first half of XX century presenting his understanding about democracy and education in a complex society. At the second one, we approach the concepts of interaction, continuity, interest and effort, because they guide the author’s formulations about the conception of educative experience. Finally, at the third one, we analyze the conception of educative experience shown by the author synthesized as a result of the effort of the human intelligence who connect the contemporary experience with the historical experience. We prioritized as a source of our research the essays: Interest and effort (1895), My Pedagogic Creed (1897), The School and Society (1899), Democracy and Education (1916), Reconstruction in Philosophy (1920) and Experience and Education (1938). About the research results, we show especially that for Dewey, there is a close connection between practical experience and historical knowledge, being these two elements the base of school education, fundamental space of individual formation and development and conservation of democratic life at the society.